Экономические предпосылки переселения эстонских крестьян в Крым во второй половине XIX в - Маковский, В.В.; Сухарев, М.В. (Культура народов Причерноморья, 2014)
В статье рассматривается вопрос об экономических причинах переселения крестьян
Эстляндской губернии на Крымский полуостров в 60-е гг. XIX в. Анализируется тяжёлое социально-
экономическое положение эстонского крестьянства в дореформенный период, формы его феодальной
эксплуатации местной немецкой аристократией. Показаны благоприятные для земледельцев условия
хозяйствования в Крыму и меры содействия заселению полуострова со стороны чиновников
Таврической губернии, побудившие эстонских крестьян из лютеранской секты малтсветовцев
переселиться на крымские земли. У статті розглядається питання про економічні причини переселення селян Естляндської
губернії на Кримський півострів у 60-ті рр. ХІХ ст. Аналізується тяжке соціально-економічне
становище естонського селянства в дореформений період, форми його феодальної експлуатації
місцевою німецькою аристократією. Показано сприятливі для землеробів умови господарювання в
Криму та допоміжні засоби щодо заселення півострова з боку посадовців Таврійської губернії, які
суттєво вплинули на бажання естонських селян з лютеранської секти малтсветівців переселитися на
кримські землі. In article the question of the economic reasons of resettlement of peasants of the Estlyandsky
province on the Crimean peninsula in the 60th of the XIX century is considered. Heavy economic and social
situation of Estonian peasantry during the prereform period, forms of its feudal exploitation is analyzed by the
local German aristocracy. Managing conditions, favorable for farmers, in the Crimea and the measures of
assistance to settling of the peninsula from officials of the Taurian province which induced Estonian peasants to
move from Lutheran sect of maltsvetovets on the Crimean lands are shown.
Authors of article describe features of land tenure and land use in the Estlyandsky province of Ostzeysky edge in
the first half of the XIX century. It is noted that absolute masters of land resources in Baltic during this period
were the German barons. Though in 1816 Estonian peasants received a personal liberty from serf dependence,
their economic dependence on landowners only amplified. All land remained in property of the German
aristocracy, and volumes of auxiliary works on corvee for peasants significantly grew. The bulk of Estonian
peasants lived in conditions of extreme poverty. Situation for them was complicated by low fertility of local soils.
Resettlement of Estonians to the Crimea had also confessional basis. Yukhan Maltsvet's preacher and followers
of his community were exposed in the homeland to prosecutions from the authorities and Lutheran church. It
also in many respects promoted acceptance of a final decision on moving of members of sect to the Taurian
province.